Soil Identification using Field Electrical Resistivity Method. (May 2015) - Hazreek, Z A M; Rosli, S; Chitral, W D; Fauziah, A; Azhar, A T S; Aziman, M; Ismail, B
Abstract: Geotechnical site investigation with particular reference to soil identification was important in civil engineering works since it reports the soil condition in order to relate the design and construction of the proposed works. In the past, electrical resistivity method (ERM) has widely being used in soil characterization but experienced several black boxes which related to its results and interpretations. Hence, this study performed a field electrical resistivity method (ERM) using ABEM SAS (4000) at two different types of soils (Gravelly SAND and Silty SAND) in order to discover the behavior of electrical resistivity values (ERV) with type of soils studied. Soil basic physical properties was determine thru density (p), moisture content (w) and particle size distribution (d) in order to verify the ERV obtained from each type of soil investigated. It was found that the ERV of Gravelly SAND (278 Ωm & 285 Ωm) was slightly higher than SiltySAND (223 Ωm & 199 Ωm) due to the uncertainties nature of soils. This finding has showed that the results obtained from ERM need to be interpreted based on strong supported findings such as using direct test from soil laboratory data. Furthermore, this study was able to prove that the ERM can be established as an alternative tool in soil identification provided it was being verified thru other relevance information such as using geotechnical properties.